Actinobacteria resistant to contaminants of emerging concern - Gonzalez Holc, Victoria Guadalupe (2022)
The Contaminants of Emerging Concern (CECs) are synthetic or naturally occurring chemicals that are not commonly monitored in the environment, but have the potential to enter the environment and cause adverse ecological and/or health effects. A promising technology to clean up environments contaminated with CECs is bioremediation using actinobacteria, which are microorganisms with great metabolic diversity and ability to detoxify different organic and inorganic compounds. In this context, the objective of the present work was to select actinobacteria resistant to CECs of regional relevance. The resistance to CECs of 12 actinobacterial strains, previously isolated from contaminated environments, was qualitatively evaluated. The CECs studied were Diclofenac (DIC), Sildenafil (SIL) and Ivermectin (IVE). These CECs were selected because they were detected in several domestic and hospital effluents in the northwestern region of Argentina, and they belong to different chemical groups. The qualitative screening assay was carried out in Petri dish plates containing 20 ml of casein starch agar medium (CSA). For the DIC and SIL assays, rectangular troughs (1.5 x 6 cm) were cut in the centre of plates and filled with 1 mL of the solution to be tested. For the IVE assays, due to its insolubility, the solution was added directly to the CSA medium. The concentrations tested were: 1, 5 and 10 mg/mL. The strains were inoculated perpendicular to the rectangular troughs (DIC, SIL) or equidistant (IVE). Plates were incubated at 30 ºC for 7 days. Control plates were also performed, using sterile distilled water instead of CECs. For each strain, growth, spore formation and pigment production were evaluated in comparison to that observed on control plates. For DIC and SIL, 2 strains, different for each CEC, were able to grow, form spores and produce pigments, at levels comparable to their corresponding controls. For IVE, 12 strains were able to grow and produce pigments, but only 9 of them formed spores. None of the strains studied showed tolerance to the three CECs, although several strains showed tolerance to 2 CECs. These results demonstrate the great potential of actinobacteria to grow in presence of several types of CECs, also indicating that the metabolic pathways involved in each type of tolerance may be different. The strains with the highest resistance to each CEC were selected for degradation tests in liquid culture media, in order to evaluate their ability to use the CEC as the only source of carbon and energy.